2022
DOI: 10.1111/gcb.16492
|View full text |Cite
|
Sign up to set email alerts
|

Adult male birds advance spring migratory phenology faster than females and juveniles across North America

Abstract: Advances in spring migratory phenology comprise some of the most well-documented evidence for the impacts of climate change on birds. Nevertheless, surprisingly little research has investigated whether birds are shifting their migratory phenology equally across sex and age classes-a question critical to understanding the potential for trophic mismatch. We used 60 years of bird banding data across North Americacomprising over 4 million captures in total-to investigate both spring and fall migratory phenology fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 72 publications
(155 reference statements)
1
10
0
Order By: Relevance
“…Notably, when one insect species is excluded, five species with sex dissimilarity indicated that reproductive phenology of males was more variable than that of females (three birds, Gordo et al 2013, Harnos et al 2015, Hedlund et al 2015; two amphibians, Chadwick et al 2006). This pattern accords well with a recent finding that males are more likely to advance their breeding migration phenology than females across 36 bird species (Neate‐Clegg and Tingley 2023). Although data are very limited, this pattern clearly contrasts with the conventional view that females are more likely to shift reproductive phenology than males (Ball and Ketterson 2008, Chmura et al 2020).…”
Section: Literature Reviewssupporting
confidence: 92%
See 1 more Smart Citation
“…Notably, when one insect species is excluded, five species with sex dissimilarity indicated that reproductive phenology of males was more variable than that of females (three birds, Gordo et al 2013, Harnos et al 2015, Hedlund et al 2015; two amphibians, Chadwick et al 2006). This pattern accords well with a recent finding that males are more likely to advance their breeding migration phenology than females across 36 bird species (Neate‐Clegg and Tingley 2023). Although data are very limited, this pattern clearly contrasts with the conventional view that females are more likely to shift reproductive phenology than males (Ball and Ketterson 2008, Chmura et al 2020).…”
Section: Literature Reviewssupporting
confidence: 92%
“…courtship and breeding migration), which should be assessed in the context of sexual match/mismatch hypothesis. Indeed, a recent study has shown that males are more likely to advance their breeding migration phenology than females across 36 bird species (Neate‐Clegg and Tingley 2023), which contradicts the conventional view that females should exhibit more plastic responses to climate change (Ball and Ketterson 2008, Chmura et al 2020). Overall, although climate change‐induced phenological shifts are likely sex‐specific, many questions remain such as which sex is more likely to shift phenology under climate change, what determines it, and how sex‐specific phenological shifts can mediate seasonal population dynamics and long‐term demographic trends.…”
Section: Biological Rationale For Sex‐specific Phenological Shiftsmentioning
confidence: 95%
“…The uncoupling of community interactions as a result of asynchronous phenological responses to climate change has been raised as a conservation concern [2,5153]. Lane et al .…”
Section: Discussionmentioning
confidence: 99%
“…The uncoupling of community interactions as a result of asynchronous phenological responses to climate change has been raised as a conservation concern [2,[51][52][53]. Lane et al [19] found that female Columbian ground squirrels plastically delay emergence from hibernation in response to delayed snowmelt, but a lack of similar information on males has prevented an understanding of potential desynchrony between the sexes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, as migratory bird species shift to earlier breeding and nesting dates, they exhibit mismatched timing to peak vegetation and associated insect biomass, reducing prey availability (Visser and Both, 2005;Moore, 2011;Mayor et al, 2017). Conversely, similar species or populations of the same species have not changed the timing of their migration and nesting activities in the face of climate change, illustrating that populations or individuals within the same or similar species may react differently to changing climate conditions (Visser and Both, 2005;Moore, 2011;Neate-Clegg and Tingley, 2022). Other species of birds and insects have ceased migrations in recent years and instead remain year-round at midlatitude sites that were previously used as stop-over locations (Groepper et al, 2008;Pulito and Berthold, 2010;Moore, 2011;Satterfield et al, 2018).…”
Section: Introductionmentioning
confidence: 99%